Goodbye to all that [videorecording (DVD)] - MacLachlan, Angus; Schneider, Paul, 1976-; Camp, Anna, 1982-; Lynskey, Melanie; Scott, Audrey P. (MPI Media, 2015)
A newly single dad navigating the good, the bad, and the weird of the 30-something singles scene in the whip-smart comedy. When his wife unexpectedly informs him that she wants a divorce, well-meaning but oblivious husband Otto Wall finds himself thrust back into bachelorhood. What follows is a hilarious sequence of romantic encounters, from reconnecting with a former crush to online dating, as Otto searches for a real connection amidst a string of one night stands.